Lithuanian–Latvian Local Border Traffic, 1919–1939 - Nekrašas, Leonas (Lietuvos istorijos studijos, 2019)
Today, both Lithuania and Latvia are part of the Schengen Area, which means their citizens can freely travel between these states. The situation was different during the interwar years: the border between these Baltic Republics was strictly guarded, and traveling abroad was more complex. However, the order crossing for local residents of the border area was simplified by the local border traffic regime agreed upon by both countries. This paper aims to explore the evolution of Lithuanian-Latvian local border traffic policy in the interwar period and its impact on locals (primarily on Lithuania’s side). In the first few years after the establishment of the new states, border crossings for residents of Lithuania’s border area were regulated by internal state legislation. Initially, people were devastated by the requirement to cross the border only at sparsely placed border crossing points, the restrictions on trade, and the radical reduction of the border area. After the peaceful settlement of the Lithuanian-Latvian border in 1921, newly signed bilateral treaties began to solve the crucial problems of the locals. However, there were instances of bilateral friction and various incidents; authoritarian state structures also had reservations based on the issue of potentially unfavorable foreign influences. The breakthrough in the diplomatic relations between Lithuania and Latvia in the 1930s saw a new level of liberalization of the local border traffic policy. A positive impact was widely felt among the locals. However, certain economic concerns made this new policy short-lived. In the interwar years, grievances and discontent toward the new border relations were gradually replaced by acceptance and adaptation. Bilateral cooperation made it possible to react to and suit the needs of the people. The overall Lithuanian-Latvian local border traffic regime showed a tendency of liberalization over time, a process which was curtailed by certain political and economic realities and considerations.
Keywords: local border traffic; borderland; Lithuania; Latvia; border crossing